Characterization of the complete mitochondrial genome of Asia Corn Borer, Ostrinia furnacalis (Lepidoptera: Crambidae). Issue 1 (2nd January 2020) - Li, Chao; Li, Lili; Ren, Yanping; Lu, Zengbin; Song, Yingying; Liu, Li; Lv, Suhong; Yu, Yi; Men, Xingyuan
Abstract: In this study, the complete mitogenome sequence of Ostrinia furnacalis was described. The assembled mitogenome is 15, 241 bp in length with an extreme bias of high AT content (80.9%) (GenBank accession no. MN747041). The mitochondrial genome contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (12S rRNA and 16S rRNA) genes, and a control region (D-loop region). The mitochondrial gene order was identical to that observed in most lepidopteran genomes, nine PCGs were located on the H-strand, others were located on the L-strand. 12 PCGs were initiated by typical ATN codons, except for COI with CGA instead. 21 tRNAs had the typical cloverleaf structure, while the DHU arm of the trnS1 gene did not form a stable stem-loop structure. The 'ATAGT(A)'-like motif and a 19 bp poly-T stretch at the down-stream of the rrnS gene were observed in the A + T-rich region. The phylogenetic analysis showed that the relationship of O. furnacalis is very close to the three species in the subfamily Pyraustinae: O. nubilalis, O. penitalis and Loxostege sticticalis, and all the subfamilies of Spilomelinae, Pyraustinae, Crambinae and Nymphulinae within Crambidae formed monophyletic groups with the highest bootstrap value support.